BEYOND RELIGIOUS TOLERANCE: REFLECTING THE INTERFAITH WOMEN’S DIALOGUE - Manuain, Leryani Mince Maria; Suryaningsi Mila; Ivana Yunea Takoi (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
With its diversity in ethnicity and religion, some parts of Indonesia tend to be vulnerable to conflicts. This research aims to reveal the practice of religious tolerance and the active role of interfaith women in maintaining religious tolerance through daily dialogue. It emphasizes the significant participation of interfaith women in fostering religious tolerance. This study collected data from interfaith women in the Fatubesi subdistrict area of Kupang City using interviews and observation. The results show that interfaith women in Fatubesi, especially in the Oeba traditional market, live in harmonious and peaceful relationships. They have practiced the spirit of sisterhood and friendship in their daily encounters. Even though they are rarely involved in formal dialogue, women are active in a dialogue of life through daily interactions in informal spaces. They are connected in solidarity through openness, acceptance, respect, and helping one another. Furthermore, interfaith women are active peacekeepers through their activities of sharing food and other basic needs in their neighborhoods and during their religious celebrations. Therefore, the activism of interfaith women in the Fatubesi area is a practice that goes beyond religious tolerance.